Quantitative consequence analysis using Sedov-Taylor blast wave model. Part II: Case study in an Algerian gas industry - I SELLAMI; R NAIT-SAID; K CHETEHOUNA; C IZARRA; F Zidani (Process Safety and Environmental Protection, 2018)
In the oil and gas industry, it is common to use gas liquefaction that allows storage and transport of large quantities of LNG and LPG. One of the main disadvantages of this storage mode is the BLEVE risk, which remains a major concern for risk decision-makers. In order to prevent the occurrence of this risk and reduce its impact, risk analysts often use quantitative risk analysis (QRA), which is based on the understanding and quantification of the accidental phenomena and their consequences (overpressure, thermal radiation, toxicity dose). QRA is a rigorous and advanced approach that requires reliable data in order to obtain a good estimate and control of risks. The main objective of this paper (Part II) is to integrate the Sedov-Taylor model developed in Part I into the QRA approach in order to evaluate BLEVE blast effect, and illustrate it with a case study on a pressurized LPG accumulator located in the MPP3-plant of SONATRACH company in the Hassi R'Mel gas field (the largest gas field in Algeria). A parametric analysis of the fuel mass, temperature at failure and rupture pressure is carried out to study their influence on the evolution of BLEVE overpressure. In addition, the evaluation of BLEVE thermal effect is performed in order to better realize an exhaustive QRA. Through this application, the results show the great relevance of the Sedov-Taylor model in the consequence analysis and also in the development of process safety recommendations.